2020
DOI: 10.1111/cod.13502
|View full text |Cite
|
Sign up to set email alerts
|

Health education decreases incidence of hand eczema in metal work apprentices: Results of a controlled intervention study

Abstract: Background: Metal work apprentices (MWAs) frequently develop work-related hand eczema (HE). Objectives: To evaluate the effect of health education on incidence of work-related HE in MWAs and to assess confounding factors. Materials/methods: In a prospective controlled intervention study, 131 MWAs received educational training on prevention of HE, whereas 172 MWAs and 118 office work apprentices served as controls. At baseline and during three yearly follow-ups, questionnaires were completed and hands were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(63 citation statements)
references
References 49 publications
3
59
0
1
Order By: Relevance
“…Recently, we demonstrated in 303 metal work apprentices that FLG mutations are significantly associated with incident hand eczema during apprenticeship. 22 The rate of FLG mutation carriers in apprentices with incident hand eczema was 13.0% and thus corresponds well with the current results. In contrast to AD, FLG mutations were not associated with severity of hand eczema and not more common in TIP than in SIP patients in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Recently, we demonstrated in 303 metal work apprentices that FLG mutations are significantly associated with incident hand eczema during apprenticeship. 22 The rate of FLG mutation carriers in apprentices with incident hand eczema was 13.0% and thus corresponds well with the current results. In contrast to AD, FLG mutations were not associated with severity of hand eczema and not more common in TIP than in SIP patients in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…36 Accordingly, we recently found a significant association between tobacco smoking and incident hand eczema in metalwork apprentices. 22 However, data on associations between tobacco smoking and hand eczema are contradictory. 37 Previously we revealed that work-related hand eczema was more severe and persistent in smokers than in nonsmokers among TIP patients and that tobacco smoking was associated with work absenteeism and leaving the workforce.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could possibly be attributed to work environment, harmful effects of Hg and Pb, lack of awareness of workplace safety and the need to use PPEs (17). Furthermore, implementation of regular vocational training could reduce the burden of the disease associated with metal work apprentices (18). The effects of such exposure to metals have been observed in some related health complication as presented in Table 3.…”
Section: Discussionmentioning
confidence: 99%